Sentidos de vida e morte para meninos com experiência de moradia de rua: uma pesquisa sociopoética - Silveira, Eveline Maria Perdigão (2009)
Brazil is a country marked by violence. It has victimized a large population, particularly young age of 19, mostly black and poor. Many of these young people are on the streets in pursuit of their own living and family, while building their own way of existence, based on multiple forms of sociability. Around them circle prejudices and myths that point in different directions, but they speak of a society marked by huge social disparities, which assumes no responsibility for their own children and adolescents in situations of social vulnerability and personal, and not even recognize them as social subjects.The existence of these subjects that make up the urban territory bothers many and sometimes has led discussions on the revision of the Statute for Children and Adolescents, the need for "clean" the city, shutting them in prisons and reformatories or to exterminate them. These are ideas that are based on the notion that these children and teens are incorrigible beings, since they are accustomed to evil, do not value life and fear nothing, not even death. This thesis, Meanings of Life and Death for Children with Experience House Street, aims to discuss on the mechanisms that generate these understandings about children and adolescents with experience of street housing, endorsing on Foucault, Deleuze, Guattari and Rolnik, authors who design the socius as a factory for the production of truths, realities and subjectivities. In this perspective, it also aims to understand the meanings they attach to the young life and death, with the intention of breaking with the myths and model calculations that attempt to define them. What would life for children and adolescents who guided a complex sociality in urban space? How these young people perceive their own existence? What meanings attributed to death? What's life in death? What is death in life? Why - and what - live? Why - and what - to die? These are the questions guiding this study. As the theoretical and methodological investigation, we chose to Poetry Society because of her design thinking as an exercise in which they articulate concepts and feelings, and introduces the group as a reference in the knowledge production, defined here as the group researcher. By way of research results, the research group produced around plural concepts of life and death, which were interpreted in light of the complex thought of Morin. Among the concepts produced stand out life and death as articulated pathways to good and evil, life and hurricanes death, life-maze, game, life, death, revelation, death bridge dark, dark house, monster destroyer, expressing how much violence has marked the forms of subjectivity of children and adolescents with experience of housing street.